Analisis Faktor–Faktor Yang Mempengaruhi Pendapatan Pengusaha Eyelash Extension Di Mall Kota Surabaya - Putri Cecilia Elvira Dwi S; Kunto Inggit Gunawan (Journal Economic Excellence Ibnu Sina, 2024)
This research aims to determine the factors that influence the income of eyelash extension workers in the Surabaya City Mall. This research uses quantitative methods with questionnaire data collection techniques and observation. The method used is multiple linear regression analysis, determination analysis (R2), and hypothesis testing. This data collection technique was carried out by distributing questionnaires to 40 respondents, namely the income of eyelash extension entrepreneurs in the Surabaya City Mall. The results of this study prove that partially working capital, labor, length of business have a significant effect on the income of eyelash extension entrepreneurs in Surabaya City Mall. Simultaneously working capital, labor, length of business have a significant effect on the income of eyelash extension entrepreneurs in Surabaya City Mall.